2004
DOI: 10.1007/s00405-003-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

Indirect autofluorescence laryngoscopy in the diagnosis of laryngeal cancer and its precursor lesions

Abstract: Direct autofluorescence endoscopy of the larynx has proven to facilitate the detection and delineation of precancerous lesions, carcinoma in situ and cancer. The aim of the present study was to evaluate the diagnostic potential and limitations of this imaging technique applied during indirect laryngoscopy. In a prospective study, 116 patients with suspected precancerous or cancerous lesions were investigated preoperatively by indirect autofluorescence laryngoscopy. Autofluorescence was induced by filtered blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 14 publications
2
36
0
5
Order By: Relevance
“…However, the applicability of this method is more or less restricted because of the requirement of removing human tissues and the difficulty of real-time diagnosis. During recent 20 years, a new diagnostic modality termed ''optical biopsy'' has been developed to distinguish different tissues (or cells) by optical methods [4][5][6]. These technologies are useful for clinical diagnosis, especially when the non-invasiveness and immediate results are requested.…”
Section: Introductionmentioning
confidence: 99%
“…However, the applicability of this method is more or less restricted because of the requirement of removing human tissues and the difficulty of real-time diagnosis. During recent 20 years, a new diagnostic modality termed ''optical biopsy'' has been developed to distinguish different tissues (or cells) by optical methods [4][5][6]. These technologies are useful for clinical diagnosis, especially when the non-invasiveness and immediate results are requested.…”
Section: Introductionmentioning
confidence: 99%
“…14,17,20 Early studies of fluorescence in laryngeal lesions showed that the technique could be useful in a clinical setting, 25,27,29,32 and recent studies as well as the present study support this. 10,11,37 Technical Aspects. The present study presents an analysis of fluorescence spectra recorded from laryngeal lesions, indicating that it is possible to obtain diagnostic information of clinical impact using a few detection wavelength bands only, a technique that can be fully implemented in an imaging instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…These images taken from (Arens et al, 2004) were acquired in two different points of view with known pose as shown in Fig. 7.…”
Section: Numerical Registration Resultsmentioning
confidence: 99%